2015
DOI: 10.4252/wjsc.v7.i2.448
|View full text |Cite
|
Sign up to set email alerts
|

Importance of the stem cell microenvironment for ophthalmological cell-based therapy

Abstract: Cell therapy is a promising treatment for diseases that are caused by cell degeneration or death. The cells for clinical transplantation are usually obtained by culturing healthy allogeneic or exogenous tissue in vitro . However, for diseases of the eye, obtaining the adequate number of cells for clinical transplantation is difficult due to the small size of tissue donors and the frequent needs of long-term amplification of cells in vitro , which results in low cell viability after transplantation. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 135 publications
0
26
0
2
Order By: Relevance
“…However, the risks of potential tumor development and other unpredictable biological changes during transplantation are still unresolved. The cellular interaction of transplanted cells in the microenvironment has been reported important to obtain successful results in regeneration therapy [13] . Recently, we demonstrated that the microenvironment of cancer cells can affect stem cells to convert iPSCs into CSC-like cells, with tumorigenic capacity as well as self-renewal and differentiation potential.…”
Section: Introductionmentioning
confidence: 99%
“…However, the risks of potential tumor development and other unpredictable biological changes during transplantation are still unresolved. The cellular interaction of transplanted cells in the microenvironment has been reported important to obtain successful results in regeneration therapy [13] . Recently, we demonstrated that the microenvironment of cancer cells can affect stem cells to convert iPSCs into CSC-like cells, with tumorigenic capacity as well as self-renewal and differentiation potential.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the poor viability of transplanted BMSCs might be related to the hostile survival microenvironment 15. The vasculature plays an instructive role in the stem cell niche16 whereas a growing body of evidence has indicated that diabetes impacts angiogenesis through a variety of mechanisms, including vascular endothelial growth factor (VEGF)/phosphoinositide 3’ kinase/AKT/endothelial nitric oxide synthase (eNOS) proangiogenic pathway abrogation and vessel (CD31 + ) number reduction 1718…”
Section: Introductionmentioning
confidence: 99%
“…The microenvironment is greatly involved in the success of stem cell transplant and the long-term survival of the graft in ocular surface therapy. 23 In cultivated limbal epithelial transplantation, Tsai et al found that the intact amniotic membrane could provide the niche environment for cultured limbal stem cells and maintain the limbal-like environment, which cell survival related to the severity of the disease. 24 In general, the microenvironment has a central role in the survival and renewal of limbal stem cells.…”
Section: Discussionmentioning
confidence: 99%